Influence of Age and Pathology on Achilles Tendon Properties During a Single-leg Jump - Intziegianni, K.; Cassel, M.; Rauf, S.; White, S.; Rector, M.; Kaplick, H.; Wahmkow, G.; Kratzenstein, S.; Mayer, F. (International Journal of Sports Medicine, 2016)
Prevalence of Achilles tendinopathy increases with age leading to a weaker tendon with predisposition to rupture. Conclusive evidence of the influence of age and pathology on Achilles tendon (AT) properties remains limited, as previous studies are based on standardized isometric conditions. The study investigates the influence of age and pathology on AT properties during single-leg vertical jump (SLVJ). 10 children (C), 10 asymptomatic adults (A), and 10 tendinopathic patients (T) were included. AT elongation [mm] from rest to maximal displacement during a SLVJ on a force-plate was sonographically assessed. AT compliance [mm/N]) and strain [%] was calculated by dividing elongation by peak ground reaction force [N] and length, respectively. One-way ANOVA followed by Bonferroni post-hoc correction (α=0.05) were used to compare C with A and A with T. AT elongation (p=0.004), compliance (p=0.001), and strain were found to be statistically significant higher in C (27±3 mm, 0.026±0.006 [mm/N], 13±2%) compared to A (21±4 mm, 0.017±0.005 [mm/N], 10±2%). No statistically significant differences (p≥0.05) was found between A and T (25±5 mm, 0.019±0.004 [mm/N], 12±3%). During SLVJ, tendon responded differently in regards to age and pathology with children having the most compliant AT. Higher compliance found in healthy tendons might be considered as a protective factor against load-related injuries.
Keywords: children; tendinopathy; compliance; dynamic; ultrasonography